Pemenuhan Kebutuhan Air Bersih Dengan Sistem Rain Harvesting Di Desa Pematang Duku Kecamatan Bengkalis Kabupaten Bengkalis - Ferdina, Muthia; Sujatmoko, Bambang; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Pematang Duku is one of village in Bengkalis Distric, Bengkalis Regency. It’s difficult to find some clean water in this village, because has red brown color. The color of water will be sticky, if we use it for showerring and washing. When it rains, people collect the rain water with simple tool like bucket, but it can’t fulfill their needs for long time. In order to fulfill their needs of clean water, we need to apply technology in rain harvesting in Pematang Duku Village Bengkalis Distric, Bengkalis Regency. The research uses behavior model method that using of Rain Cycle 2 software with data input consists of daily rainfall data in a year (mm/day), effective wide of the roof (m2) coefficient of drainage from the roof and data of water needs according to the number of families (m3/day). The main result is number determination of percentage of the water that can be harvested .Keywords : Rain Harvesting Technology, Bengkalis, Rain Cylce 2 Software